What might educational leadership mean in 21st century - Ballo, Anduena (2020)
Understanding what educational leadership means remains a challenge for researchers and practitioners despite an extant body of literature focused on this field. This study investigates conceptions of educational leadership among graduates of the Master’s Degree Programme in Educational Leadership (MPEL), University of Jyväskylä (JYU). The aim of this study is to qualitatively illuminate distinct ways the participants conceptualize educational leadership. This study interprets the conceptions of educational leadership based on a framework developed to inform educational leadership scholarship theory and practice (Bush, 2011; English, 2003; Gronn, 1999; Gunter, 2001; Harris & Jones 2016; Heck & Hallinger 2005; Northouse, 2016). This qualitative empirical study uses phenomenography for the methodological framing and data analysis of eleven semi-structured interviews of graduates from MPELProgramme. The analysis illuminates five distinct categories of description that reflect the participants’ conceptions of educational leadership. The participants conceptualize educational leadership as (1) supporting students, (2) coordinating teachers, (3) guiding a group of people, (4) educating young generations, and (5) influencing citizens. This study concludes that educational leadership entails a far broader context than school leadership, and not only limited to school settings. Anyone involved in educational leadership can be perceived as an educational leader. This study closes with a discussion on the importance of understanding conceptual-level variation of educational leadership, which has clear implications in the scholarship focused in this field.